Psychometric properties of the Iranian version of Quality of Life in Epilepsy Inventory 31-Item - Ali Montazeri; Mansoureh Thoghae; Mariam Vahdaninia; Fariba Ebrahimi (Payesh, 2010)
Objective(s): Epilepsy is a common chronic disease in all ages. Quality of life in epileptic patients is of utmost importance. This study investigated the reliability and validity of the Iranian version of Quality of Life in Epilepsy Inventory-31 (QOLIE-31-P). Methods: The English version of the questionnaire was translated into Persian and then it pilot tested. The instrument includes 31 items in 7 domains. The scores range from 0-100 with higher scores indicating better conditions. The final version of the Persian questionnaire was administered to a sample of epileptic patients 18years old and over referred to the electroencephalography ward in Sina hospital (Tehran University of Medical Sciences). Reliability was estimated using "internal consistency" (Cronbachchr('39')s α) and validity was assessed using "known groups comparison". Results: In all 76 patients were studied. The mean age of the patients was 30.6 years (SD=12.2) and the mean years of their education was 9.9 (SD=4.2). The analysis showed that the domains met the minimum reliability standard, Cronbachchr('39')s α coefficient ranging from 0.71-0.89 with the exception of medication effects and social functioning (α= 0.51 & 0.65). Validity analysis showed that the instrument discriminated well between subgroups of patients who differed in "seizure types, frequency of epileptic attacks in previous month and last year". Conclusion: The Iranian version of the QOLIE-31-P is a reliable and valid measure of health-related quality of life in patients with epilepsy.